To solve the problem, we need to apply the zero power rule, which states that any non-zero number raised to the power of zero is equal to 1.
Looking at the expression:
\[ 7 / (-5.3)^0 \cdot 4 \cdot 9 \]
We apply the zero power rule to \((-5.3)^0\):
\[ (-5.3)^0 = 1 \]
Thus, we can replace \((-5.3)^0\) with 1 in our expression:
\[ 7 / 1 \cdot 4 \cdot 9 \]
Now we simplify this:
\[ 7 / 1 = 7 \]
Next, we recognize that multiplying by \(4 \cdot 9\) means we will compute that product:
\[ 4 \cdot 9 = 36 \]
So now we are left with:
\[ 7 + 36 \]
This can be represented as:
\[ 7 + 36 \]
Let's evaluate the answer options based on this conclusion:
- 7 / 1 + 4⋅9 → This simplifies to \(7 + 36\).
- 7 / 5.3 + 4⋅9 → Incorrect because we are not dividing by \(5.3\).
- 7 / 0 + 4⋅9 → Incorrect as dividing by zero is undefined.
- 7 / 5.3 with a power of 0 + 36 → Incorrect because 5.3 is not related to the zero power.
The correct equivalent expression is:
7 / 1 + 4⋅9.